Design and Development of an Oil Conditioning System for Industrial Applications (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Hydraulic and lubrication systems are commonly used in industrial applications for power transmission, lubrication, cooling, and motion control. The efficiency and reliability of these systems depend heavily on the cleanliness and condition of hydraulic oil. Throughout continuous operation, hydraulic oil gets contaminated with metallic wear particles, moisture, air, sludge, and oxidation products, leading to issues like abrasive wear, pressure instability, cavitation, internal leakage, and early failure of hydraulic components. This research aims to design and develop an Oil Conditioning System (OCS) for industrial hydraulic applications by using offline kidney-loop depth filtration technology. The system uses cellulose-based depth filtration media for ongoing hydraulic oil conditioning and contamination control. The experimental setup targets improving hydraulic oil cleanliness according to ISO 4406 standards, lowering particulate contamination, controlling moisture, and boosting hydraulic system reliability. Experimental analysis shows a significant drop in contamination levels, better ISO cleanliness codes, reduced moisture, and improved hydraulic oil quality. The proposed Oil Conditioning System enhances machine reliability, lengthens hydraulic oil service life, decreases maintenance frequency, minimises downtime, and facilitates predictive maintenance in modern industrial settings.